LITERATURE REVIEW PEMBELAJARAN PENDIDIKAN JASMANI MELALUI MODEL PENDIDIKAN GERAK - Syaefullah Ambiya, - (2020)
This research is motivated by the lack of movement education models used, there are still many teachers applying command-style models, therefore researchers are interested in the problems faced in learning physical education, sports and health. The purpose of this study was to determine that the basic motion education model has an effect on learning physical education in elementary schools. The method used is the Literature Review, using secondary data which requires the use of a source or a questionnaire instrument (questionnaire). The research sample used is the level of education from the elementary school level. The total number of previous research articles used was 11 articles (National and International). The results showed that the basic movement education model was effective and influential in learning physical education and on the skills of all samples. And this mobile education model is very suitable for use at the elementary school level.